Ответ: (a/ab-b2 + b/a2-ab) * a2b-ab2/a2+b2=1
(a/b(a-b) + b/a(a-b)) * ab(a-b)/(a-b)(a+b)=1
a2+b2/ab(a-b) * ab(a-b)/(a-b)(a+b)=1
(a+b)(a+b)/(a-b)(a+b)=1
a+b/a-b=1
Объяснение: b2 это b в квадрате также как и в остальных a2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: (a/ab-b2 + b/a2-ab) * a2b-ab2/a2+b2=1
(a/b(a-b) + b/a(a-b)) * ab(a-b)/(a-b)(a+b)=1
a2+b2/ab(a-b) * ab(a-b)/(a-b)(a+b)=1
(a+b)(a+b)/(a-b)(a+b)=1
a+b/a-b=1
Объяснение: b2 это b в квадрате также как и в остальных a2